Localized incompletely resected standard risk rhabdomyosarcoma in children and adolescents: Results from the European Paediatric Soft Tissue Sarcoma Study Group RMS 2005 trial - Mandeville, Henry C; Bisogno, Gianni; Minard-Colin, Veronique; Alaggio, Rita; Ben-Arush, Myriam; Chargari, Cyrus; Coppadoro, Beatrice; Craigie, Ross; Devalck, Christine; Ferman, Sima; Ferrari, Andrea; Glosli, Heidi; et al. (Cancer, 2024)
BACKGROUND: The authors report the prospective evaluation of reduced dose alkylator chemotherapy combined with radiotherapy for European Pediatric Soft Tissue Sarcoma Study Group (EpSSG) standard risk nonalveolar rhabdomyosarcoma (NA-RMS). PATIENTS AND METHODS: Localized node negative Intergroup Rhabdomyosarcoma Study (IRS) II/III NA-RMS at favorable sites (subgroup C), <25 years old, received five cycles of ifosfamide, vincristine, and dactinomycin (IVA) chemotherapy (30 g/m2 ifosfamide) and four cycles of vincristine and dactinomycin (if receiving radiotherapy), or nine cycles of IVA (54 g/m2 ifosfamide) ± radiotherapy. Delayed primary tumor excision was considered for IRS III tumors. The primary end points were event-free survival (EFS) and overall survival (OS). RESULTS: From October 2005 to December 2016, 359 evaluable patients were recruited: orbit, 164 (45.7%); head and neck nonparameningeal, 77 (21.4%); and genitourinary non-bladder/prostate, 118 (32.9%). EFS and OS were 77.4% (95% confidence interval [CI], 72.5-81.6) and 93.5% (95% CI, 90.1-95.8), respectively. Lower dose alkylator chemotherapy and radiotherapy achieved 5-year OS of 93.7% but the difference with higher dose alkylator chemotherapy +/- radiotherapy was not significant (p = 0.8003). Adjuvant radiotherapy improved EFS with 5-year estimates of 84.7% versus 65.2% for nonirradiated (p < .0001), but not OS (p = .9298). Omitting radiotherapy for orbital tumors reduced OS (5-year was 87.1% vs. 97.3% for irradiated, p = .0257). Following R0 resection (n = 60), radiotherapy did not significantly improve EFS or OS. CONCLUSIONS: Radiotherapy for local tumor control allows for reduction of cumulative dose of alkylators in EpSSG standard risk subgroup C RMS patients. The omission of radiotherapy did not affect OS in all patients except those with orbital RMS and was associated with inferior EFS.
Keywords: alkylator chemotherapy; Rhabdomyosarcoma; rhabdomyosarkom; Humans; Infant; Vincristine; ifosfamid; kojenec; dítě; Dactinomycin; Child; Female; mladý dospělý; pediatric sarcoma; protokoly protinádorové kombinované chemoterapie; lidé; Europe; daktinomycin; Ifosfamide; předškolní dítě; ženské pohlaví; Male; vinkristin; Adolescent; surgical resection; Antineoplastic Combined Chemotherapy Protocols; Young Adult; rhabdomyosarcoma; mužské pohlaví; prospektivní studie; Child, Preschool; Evropa; radiotherapy; mladiství; Prospective Studies